2022
DOI: 10.17221/281/2021-pse
|View full text |Cite
|
Sign up to set email alerts
|

Copper content in soils and litter from fruit orchards in Central Chile and its relationship with soil microbial activity

Abstract: This study assessed both the soil and litter copper (Cu) levels and their relationships with soil microbial activity, in fruit-tree production areas of central Chile where Cu-based pesticides are intensively sprayed. Samples of soil (0–20 cm depth) and litter from a number of selected orchards (kiwi, table grape, plum, and cherry) were collected and analysed for their Cu content and C-induced soil microbial activity. Results showed that the mean total soil Cu level was 225 mg/kg and soluble soil Cu was less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Notably, only the total soil Cu concentration exhibited a wide range of variation (up to 24× higher). However, the soil soluble Cu content exhibited a negligible variation (less than 1×), with a mean value of 0.16 mg kg − 1 , which is the same value obtained in a previous study by Schoffer et al 2022 that was conducted in the same region. As discussed previously, the topsoil in the study region is in uenced by Cu-mining activity, as indicated by the polymetallic (Cu, Zn, As, and Pb) pollution detected in the soil, which is in agreement with corresponding literature related to the study area 26 .…”
Section: Resultssupporting
confidence: 87%
“…Notably, only the total soil Cu concentration exhibited a wide range of variation (up to 24× higher). However, the soil soluble Cu content exhibited a negligible variation (less than 1×), with a mean value of 0.16 mg kg − 1 , which is the same value obtained in a previous study by Schoffer et al 2022 that was conducted in the same region. As discussed previously, the topsoil in the study region is in uenced by Cu-mining activity, as indicated by the polymetallic (Cu, Zn, As, and Pb) pollution detected in the soil, which is in agreement with corresponding literature related to the study area 26 .…”
Section: Resultssupporting
confidence: 87%
“…The highest enzyme activity and AWCD in the root zone can be associated with a high microbial biomass and organic matter, as well as lower Cu content as shown by relationships between CFUs, enzyme activities (except for AA), and total and available Cu contents (Figure 3). The positive effect of organic matter (slightly higher in the root zone) on soil biological activity has been widely described [64] even in metal contaminated soils [65]. In this context, organic matter serves as a substrate for heterotrophic microorganisms [66] and facilitates the creation of enzyme-humus complexes that mitigate the proteolytic and thermal degradation of extracellular enzymes (e.g., Pacid and UA) [67].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the plant litter from this experimental site was not analysed. However, evidence from the literature has shown that, generally, the plant litter from orchards receiving Cu sprays have a higher Cu concentration than the soils [35][36][37]. For example, Schoffer et al [36] reported that the leaf litter total Cu content from different fruit orchard farms receiving Cu-based fungicide sprays in Chile was 3-7 times higher than the total soil Cu.…”
Section: Influence Of Different Soil Properties On Soil Cu Concentrat...mentioning
confidence: 99%